Ingrowing Hair: A Case Report. Issue 19 (May 2016) - Luo, Di-Qing; Liang, Yu-Hua; Li, Xi-Qing; Zhao, Yu-Kun; Wang, Fang; Sarkar, Rashmi
Abstract : Abstract: Cutaneous pili migrans and creeping eruption caused by parasitic diseases may present as a moving linear lesion in skin. The former, caused by a hair shaft or fragment embedded in the superficial skin or middle dermis, is a rare condition characterized by creeping eruption with a black line observed at the advancing end. In exceptionally rare instance, the hair grows inside the skin and burrows in the uppermost dermis, such a condition has been called "ingrown hair." We report a 30-year-old Chinese man, who was accustomed to pull or extrude the beard hairs, with 1-year history of slowly extending black linear eruption on his right chin. Cutaneous examination revealed a 4-cm long black linear lesion beneath the skin associated with edematous erythema around and folliculitis on both ends of the lesion. After treatment with topical mupirocin ointment, the erythema and folliculitis improved and 2 hairs of the beard with hair follicles were pulled out from the skin. Two weeks later, another similar black line about 1 cm in length in the skin presented on the prior lesional area, which was pulled out by a shallow incision of the skin and was also demonstrated as a beard hair with hair follicle. The patient was diagnosed as "ingrowing hair" with multiple recurrences. The lesions recovered after the beard hairs were pulled out. No recurrence occurred in a year of follow-up. We suggest that "ingrowing hair" is better than "ingrown hair" to describe such a condition. Pulling out the involved hair and correcting the bad practice are its optimal management strategies.